Establishment of an Efficient and Flexible Genetic Manipulation Platform Based on a Fosmid Library for Rapid Generation of Recombinant Pseudorabies Virus - Zhou, Mo; Abid, Muhammad; Yin, Hang; Wu, Hongxia; Teklue, Teshale; Qiu, Hua-Ji; Sun, Yuan (Frontiers in Microbiology, 2018)
Conventional genetic engineering of pseudorabies virus (PRV) is essentially based on homologous recombination or bacterial artificial chromosome. However, these techniques require multiple plaque purification, which is labor-intensive and time-consuming. The aim of the present study was to develop an efficient, direct and flexible genetic manipulation platform for PRV. To this end, the PRV genomic DNA was extracted from purified PRV virions and sheared into approximated 30-45 kb DNA fragments. After end-blunting and phosphorylation, the DNA fragments were separated by pulsed field gel electrophoresis, the recovered DNA fragments were inserted into the cloning-ready fosmids. The fosmids were then transformed into Escherichia coli and selected clones were end-sequenced for full-length genome assembly. Overlapping fosmid combinations that cover the complete genome of PRV were directly transfected into Vero cells and PRV was rescued. The morphology and one-step growth curve of the rescued virus were indistinguishable from those of the parent virus. Based on this system, a recombinant PRV expressing EGFP fused with the VP26 gene was generated within two weeks, and this recombinant virus can be used to observe the capsid transport in axons. The new genetic manipulation platform developed in the present study is an efficient, flexible and stable method for the study of the PRV life cycle and development of novel vaccines.